Tuning polylactic acid performance using green citrate plasticizers of varying chain lengths - Lazaro Hdez, Carlos (2025)
The addition of these plasticizers increases the chain mobility of PLA, enhancing its deformability while reducing both tensile strength and elastic modulus. Mechanical testing identified TEC at 20 wt% as the most effective formulation, achieving an elongation of 307 % and a reduction in tensile strength from 70.6 MPa (PLA) to 25.2 MPa. Formulations containing 10 wt% exhibited anti-plasticization effects, with a slight reduction in elongation from 3.4 % to 3.2 %. Thermal and thermomechanical analyses corroborated the plasticizing effect, demonstrating a decrease in glass transition temperature from 59.6 °C to 19.3 °C, which indicates sufficient chain mobility to attain a rubber-like state at room temperature. Enhanced mobility also promoted crystallization by modifying nucleation behavior, altering crystal growth dimensionality, and reducing the activation energy required. Shape memory characterization revealed a rapid initial recovery in plasticized samples; however, total recovery diminished at higher plasticizer contents near 20 %, while lower concentrations exhibited recovery rates close to 90 %. Due to their low molecular weight of the plasticizers, migration is anticipated, resulting in measurable weight loss when exposed to food simulants. This migration phenomenon is associated with an increase in free volume, which also contributes to the improved ductile properties observed in plasticized PLA.